Pengaruh Corporate Governance, Kompensasi Rugi Fiskal, dan Ukuran Perusahaan Terhadap Penghindaran Pajak - Mohammad Syadeli (STKIP PGRI TULUNGAGUNG, 2022)
This study aims to examine the effect of Corporate Governance with proxy for institutional ownership, the proportion of independent commissioners, and audit committee, as well as the influence of other variables namely fiscal loss compensation and company size on tax avoidance. This research includes quantitative causality research using secondary data. The population in this study are all manufacturing companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange in 2016-2018. Sampling was determined based on the purposive sampling method to obtain 24 companies. The analytical method uses multiple linear regression analysis processed with SPSS. These results prove that the presence or absence of institutional ownership and the audit committee has no significant effect on Tax Avoidance. While, the proportion of independent board of commissioners, fiscal loss compensation, and company size has positive and significant effects on tax avoidance.